A literature review on the impact of digitalisation on management control - Jochen Fähndrich (Journal of Management Control, 2022)
Digitalisation affects management control (MC). It leads to changes in the way MC activities are organised, performed and analysed. Companies of all industries, locations and sizes have to adapt their MC to digital circumstances, starting with the understanding and delimitation of MC tasks, through the modified application of MC instruments and the consideration of behavioural aspects of MC, to the organisation of the MC function within the company. This paper presents a systematic review of the literature according to Tranfield et al. (Br J Manag 14:207–222, 2003), focusing on the impact of digitalisation on MC. A comprehensive overview of scientific literature is provided by reviewing 166 highly rated accounting journals (based on multiple international journal ratings) and analysing 116 articles from January 2000 to August 2022. Based on the MC framework developed by Guenther (J Manag Control 23:269–290, 2013), the identified studies are categorised into the following research dimensions: tasks, instruments, organisation and behavioural aspects. Multiple studies highlight the continuous development of the MC function under the impact of digitalisation, including the extension of MC tasks, the adaptation of existing MC instruments and creation of new MC instruments, positive and negative behavioural aspects of digitalisation on MC and the establishment of new MC organisation models. In addition to the qualitative content analysis, this literature review also includes an analysis of the methods applied and illustrates their changes over time. This study reveals research gaps in relation to the current MC research and presents potential starting points for future research.
Keywords: C89; D02; M40; C89; 330; Digitalisation; Management control; Management accounting; Controlling; Literature review